Erlotinib as Second-Line Therapy for Patients with Advanced Non-Small-Cell Lung Cancer and Wild-Type EGFR Tumors (Journal of Analytical Oncology, 2015)
Aim: The objective of the study was to determine the efficacy and safety of erlotinib in second-line therapy for patients with advanced non-small-cell lung carcinoma (NSCLC) and wild-type tumors, measuring progression-free survival (PFS), the response rate, and overall survival (OS).Material and Methods: This retrospective, observational, and multicenter study involved 47 patients diagnosed with NSCLC and wild-type epidermal growth factor receptor(EGFR) who received erlotinib as second-line therapy in four Spanish hospitals. Primary and secondary endpoints included the determination of the efficacy (by measuring progression-free survival, PFS, the response rate, and overall survival, OS) and safety profile of erlotinib.Results: The median PFS was 2.33 months (95% CI, 0.4-10.9). No differences in PFS were found regarding sex, age, smoking habits, ECOG performance status, and tumor histology. The median OS was 4.00 months (95% CI, 1.18-6.82). Four patients developed grade 3-4 non-hematological toxicities, including asthenia, cutaneous toxicity, and renal failure. One patient developed grade 3-4 thrombocytopenia.Conclusion: Our study corroborates the modest but clear benefit of second-line agents, including erlotinib, for the treatment of advanced NSCLC, and supports their administration in patients with wild-type EGFR. Further prospective studies involving large number of patients are required to corroborate such results.